KOMITMEN, KEBERSAMAAN DAN KINERJA - Wahyu Wicaksono (JIANA ( Jurnal Ilmu Administrasi Negara ), 2015)
Commitment, Unity and Performance. The research objective was to determine the effect of commitment and togetherness to the team performance squads extinguishing forest fires and land in Kota Dumai. The study population was a member of a team of firefighters Kota Dumai as many as 100 people and all the population sampled. Data was concluded using a questionnaire using Likert scale. Data were analyzed using multiple regression. The results showed that commitment and togetherness partially and simultaneously have a positive and significant impact on team performance firemen with 5% degree of confidence. Variable contribution commitment and togetherness in the team’s performance firemen just as much as 10.82%, while the remaining 89.12% influenced by other factors.